Alstom technology transfer experience: the case of the Korean train express (KTX). (1st September 2004) - Rouach, Daniel; Saperstein, David
More than ten years of long and intense discussions with South Korean authorities were necessary for the Franco-British consortium Alstom to win, in 1993, a major contract for the sale of 46 high-speed TGV trains (Train a Grande Vitesse) and related equipment and services to link two of the country's largest cities, Seoul and Pusan. This project, which was budgeted at US 2.1 billion, was a fantastic opportunity for Alstom to promote the TGV in the Asian markets, and to reinforce its image as a world-class firm with international experience. Representing an enormous investment in Korea's infrastructure, the high-speed train was an opportunity for Korea to train its workforce, penetrate a new industrial sector, and potentially take the lead in the high-speed train market in Asia. After two decades of steady progress, the start of the 21st century has witnessed major progress in the development of a new, dedicated high-speed rail route between the two Korean cities, and the first trains will run in 2003. The new train fleet consists of 46 high-speed trainsets, directly derived from France's TGV designs, built under a technology transfer agreement with Alstom. The first 12 trainsets were built in Belfort, France, and the others in South Korea. This paper analyses the central role of technology transfer and the stakes which had to be managed by Alstom in order to finally succeed in this project.